1986
DOI: 10.1530/jrf.0.0760435
|View full text |Cite
|
Sign up to set email alerts
|

Regional heterogeneity of human spermatozoa detected with monoclonal antibodies

Abstract: The regional antigenic heterogeneity of human spermatozoa is confirmed with 6 monoclonal antibodies raised against ejaculated human spermatozoa. The topographical localization of the antigenic determinants suggests the existence of at least 6 domains on the human spermatozoon. Different fixatives had severe detrimental effects on the antigen-antibody binding. On live human spermatozoa, each antibody bound to a distinct region: acrosome, equatorial segment, entire tail, neck, midpiece and terminal piece. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…'This work was supported by grants from DRED (contrat DRED n91-1497) and DRED (EA 975: Pouvoir fecondant des spermatozoides et r6le des lipides). 2 Alexander [11] observed mAb with immobilizing and agglutinating properties, and some antibodies are able to inhibit the binding and penetration of zona-free hamster ova by human spermatozoa in the hamster egg penetration test [12][13][14][15] or even to prevent the fertilization of human oocytes [16]. The present paper describes the characteristics of a mAb (I9G9) generated against human sperm germ cells as well as its influence on sperm-egg interaction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…'This work was supported by grants from DRED (contrat DRED n91-1497) and DRED (EA 975: Pouvoir fecondant des spermatozoides et r6le des lipides). 2 Alexander [11] observed mAb with immobilizing and agglutinating properties, and some antibodies are able to inhibit the binding and penetration of zona-free hamster ova by human spermatozoa in the hamster egg penetration test [12][13][14][15] or even to prevent the fertilization of human oocytes [16]. The present paper describes the characteristics of a mAb (I9G9) generated against human sperm germ cells as well as its influence on sperm-egg interaction.…”
Section: Introductionmentioning
confidence: 97%
“…Sperm antigens have been defined in several species, including humans. A number of antigens on human mature spermatozoa [3][4][5][6][7][8][9][10][11][12][13][14][15][16] have been identified with monoclonal antibodies (mAb) that reportedly recognize antigenically distinct subsets of human spermatozoa. Some have been involved in functional aspects; for example, Isahakia and Accepted July 21, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…These are proteins which are accessible to antibodies present in the reproductive tract secretions. Reports of several monoclonal antibodies are available which cross reacted with only the acrosome of living mouse ( 16 ), human (17) and guineapig sperm (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although monoclonal antibodies are specific to a particular molecule they may also recognize epitopes shared by many molecules ( 17). Monoclonal antibodies labelling only one domain were reported to immunoprecipitate proteins of more than one molecular weight from that of other domains (22).…”
Section: Discussionmentioning
confidence: 99%
“…The spermatozoon is one of the cell types in which regional differentiation was demonstrated (for reviews see Bedford & Cooper, 1978;Koehler, 1978Koehler, , 1981Yanagimachi, 1981;Nicolson, 1982;Bellvé & O'Brien, 1983). Using monoclonal antibodies, we have demonstrated that particular antigens are restricted in a minimum of 6 domains on live human spermatozoa (Villarroya & Scholler, 1986a). One of them, HS 1A.1 antigen, localized on the plasma membrane over the acrosome, might be involved in subtle changes occurring during capacitation, and might help to visualize the loss of the acrosomal cap during the acrosome reaction.…”
Section: Introductionmentioning
confidence: 99%